Etnozoologi terhadap Pemanfaatan Hewan sebagai Pengobatan Tradisional di Desa Sambulangan Kecamatan Bulagi Utara Kabupaten Banggai Kepulauan - Wahyudin Abdul Karim; Mohamad Fahri Haruna; Ridriksan Solani Ndekano; Firga Nabila Lige (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Traditional medicine is treatment or treatment with ingredients or ingredients in the form of plant, animal, mineral, preparations of galenic or a mixture of these materials whose treatment refers to experience, according to skills from generation to generation, or education/training, and is applied according to the norms prevailing in society. The traditional use of animals is deliberately carried by the community to overcome health problems. The study aims to determine the types of medicinal animals and diseases that can be cured by the use of animals as traditional medicine in Sambulangan Village, North Bulagi District, Banggai Islands Regency. The type of research used in this study is descriptive qualitative, this research was carried out from July to August 2021, located in Sambulangan Village, North Bulagi District, Banggai Islands Regency. The population in this study were all types of animals used as ingredients for traditional medicine in Sambulangan Village. The samples in this study were individuals of each type of animal used as ingredients for traditional medicine in Sambulangan Village. The method of taking sample data is by using the purposive sampling method. Techniques in collecting data using interviews, surveys and documentation. Data were analyzed using qualitative descriptive analysis. The results of the study identified several types of medicinal animals and diseases that could be cured by the use of medicinal animals in Sambulangan Village, North Bulagi District, Banggai Islands Regency. There were 10 types of medicinal animals, namely monitor lizard (Varamussp.), snake (Malayophytonsp.), sand crab (Myrmeleonsp.), carthworm (Lumbricus sp.), honey bee (Apissp.), ayam kampung (Gallus gallussp.), cuscus (Ailuropssp.), snail (Achatinasp.), dubia roach (Blapticasp.), snakehead fish (Channasp.), and diseases that can be treated using these medicinal animals, namely internal diseases in general, liver disease, asthma, heart disease, surgical wounds, cough, gout, ulcers, typhoid, and toothache.